2020
DOI: 10.1002/smll.201906432
|View full text |Cite
|
Sign up to set email alerts
|

Confined Heteropoly Blues in Defected Zr‐MOF (Bottle Around Ship) for High‐Efficiency Oxidative Desulfurization

Abstract: The Keggin-type polyoxometalates (POMs) are effective catalysts for oxidative desulfurization (ODS) and confining these POMs in metal-organic frameworks (MOFs) is a promising strategy to improve their performances. Herein, postsynthetic modification of POMs confined in MOFs by adding thiourea creates more unsaturated metal sites as defects, promoting ODS catalytic activity. Additional modification by confining 1-butyl-3-methyl imidazolium POMs in MOFs is performed to obtain higher ODS activity, owing to the af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 50 publications
2
87
0
Order By: Relevance
“…Notably, Wang and coauthors recently reported that weak IR and Raman signals related to PMo12 with Keggin structure were detected in the spectra of a hybrid material composed of phosphomolybdic acid and UiO-66, which was synthesized by a similar one-pot solvothermal method as adopted in this work [26,27]. Moreover, the presence of Keggin-type PMo12 clusters in the hybrid composite was further confirmed by combining the characterization results of 31 P NMR spectra, demonstrating that the basic POM structure remained intact after being incorporated into ZrMOFs using the solvothermal synthesis process [26,27].…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
See 3 more Smart Citations
“…Notably, Wang and coauthors recently reported that weak IR and Raman signals related to PMo12 with Keggin structure were detected in the spectra of a hybrid material composed of phosphomolybdic acid and UiO-66, which was synthesized by a similar one-pot solvothermal method as adopted in this work [26,27]. Moreover, the presence of Keggin-type PMo12 clusters in the hybrid composite was further confirmed by combining the characterization results of 31 P NMR spectra, demonstrating that the basic POM structure remained intact after being incorporated into ZrMOFs using the solvothermal synthesis process [26,27].…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
“…The typical synthesis is shown in Scheme 1. According to the coordination modulation mechanism of UiO-66 synthesis revealed in literature [26,27,35], various acids such as saturated monocarboxylic acid (e.g., acetic acid), benzoic acid, and hydrochloric acid could be used as modulator. In previous work [25], it was observed that POM@UiO-66 composites with controllable morphology and crystallinity could easily be obtained when hydrochloric acid was used as modulator.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“… ( a ) Keggin-type structure of H 3 PMo 12 O 40 with differently coordinated oxygen. ( b ) Structure of UiO-66 with a Zr 6 O 4 (OH) 4 (CO 2 ) 12 cluster [ 29 ]. …”
Section: Figures Schemes and Tablesmentioning
confidence: 99%